2017
DOI: 10.1103/physreve.96.052216
|View full text |Cite
|
Sign up to set email alerts
|

Transition to synchrony in degree-frequency correlated Sakaguchi-Kuramoto model

Abstract: We investigate transition to synchrony in degree-frequency correlated Sakaguchi-Kuramoto (SK) model on complex networks both analytically and numerically. We analytically derive self-consistent equations for group angular velocity and order parameter for the model in the thermodynamic limit. Using the self-consistent equations we investigate transition to synchronization in SK model on uncorrelated scale-free (SF) and Erdős-Rényi (ER) networks in detail. Depending on the degree distribution exponent (γ) of SF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 36 publications
(70 reference statements)
1
12
0
Order By: Relevance
“…Because this repulsive synchronization, therefore, cannot be characterized by the order parameter r, we introduce the dispersion of effective frequencies σ to describe it. However, since σ is defined statistically, the Chaos ARTICLE scitation.org/journal/cha classical analysis 25 cannot be used, hence a new approach is expected in the future. The repulsive synchronization is found to exist in complex networks with different structures, such as BA, ER, scale-free networks, and small-world networks, so may be prevalent in complex networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because this repulsive synchronization, therefore, cannot be characterized by the order parameter r, we introduce the dispersion of effective frequencies σ to describe it. However, since σ is defined statistically, the Chaos ARTICLE scitation.org/journal/cha classical analysis 25 cannot be used, hence a new approach is expected in the future. The repulsive synchronization is found to exist in complex networks with different structures, such as BA, ER, scale-free networks, and small-world networks, so may be prevalent in complex networks.…”
Section: Discussionmentioning
confidence: 99%
“…Futhermore, it has shown that with the repulsive interactions, the system will turn to partial synchronization from fully synchronized state, and also traveling wave is observed. 23 Recently, some works have investigated about synchronizing phase frustrated Kuramoto oscillators [24][25][26] and found a complex relationship between the phase shifts and the synchronization phase transition. In these works, the phase shift is focused on the range of [0, π/2].…”
Section: Introductionmentioning
confidence: 99%
“…is the DC bias current. It is to be mentioned that the isolated RSCJ model has similarities with the Sakaguchi-Kuramoto phase model with inertia [43][44][45] and also with the working model of a power grid [46]. In the absence of coupling ( = 0) and a = 1.5, each node can reveal two types of dynamics: oscillatory spiking behavior (I i > 1.0) and a quiescent state (I i < 1.0).…”
Section: Prediction Of Bursting and Clustering: Network Of Josepmentioning
confidence: 99%
“…Equation ( 2) describes a set of Kuramoto-Sakaguchi oscillators in a star network with the assumption of frequencyweighted correlations [24][25][26][27][28]. Since the Kuramoto-like model in the star network with frequency-degree correlation is given byφ…”
Section: Stationary Solutions and Their Stabilitymentioning
confidence: 99%